Long‐term outcome of primary percutaneous stent angioplasty for pediatric posttransplantation portal vein stenosis. Issue 9 (20th May 2022) - Bukova, Mila; Funken, Dominik; Pfister, Eva‐Doreen; Baumann, Ulrich; Richter, Nicolas; Vondran, Florian F. W.; Happel, Christoph M.; Bertram, Harald
Abstract: This study aims to evaluate the long‐term efficacy and reintervention rate after primary percutaneous portal vein stent angioplasty for portal vein stenosis (PVS) in pediatric liver transplantation (LT) recipients. From 2004 to 2020, a total of 470 pediatric LTs were performed in our center. All cases were screened for interventional PVS treatment and analyzed retrospectively. We identified 44 patients with 46 percutaneous angioplasties for posttransplantation PVS. The median interval from LT to percutaneous catheter intervention was 5 months (16 days–104 months) with a median follow‐up (f/u) period after catheter intervention of 5.7 years (2–156 months). In 40 patients, an endovascular stent was placed as primary ( n  = 38) or secondary ( n  = 2) intervention. The median age at stent placement was 23 (6–179) months with a median weight of 10 kg (6–46 kg). Technical success and relief of PVS were achieved in all patients irrespective of age or weight. Adverse events occurred peri‐interventionally in two patients and were resolved with standard care. All primary portal vein (PV) stents remained patent until the end of f/u. Reinterventions have been successfully performed in 10 patients for suspected or proven restenosis, resulting in a primary patency rate of 75% and an assisted patency rate of 25%. The median time to reintervention was 6.2 years (range 1–10 years). The need for reintervention was independent of age or weight at both transplantation and initial angioplasty as well as of additional risk factors due to portal hypertension. Percutaneous transhepatic PV stent angioplasty in children is safe and effective in all age groups, with excellent long‐term patency. Primary stent angioplasty should be considered as first‐line treatment for PVS after pediatric LT.